2007
DOI: 10.1210/en.2007-0305
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Testosterone Exposure Results in Insulin Resistance, Enlarged Mesenteric Adipocytes, and an Atherogenic Lipid Profile in Adult Female Rats: Comparisons with Estradiol and Dihydrotestosterone

Abstract: Postnatal events contribute to features of the metabolic syndrome in adulthood. In this study, postnatally administered testosterone reduced insulin sensitivity and increased the mesenteric fat depot, the size of mesenteric adipocytes, serum levels of total cholesterol, low-density lipoprotein cholesterol, and triglycerides, and the atherogenic index in adult female rats. To assess the involvement of estrogen and androgen receptors in these programming effects, we compared testosterone-exposed rats to rats exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
70
1
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 45 publications
12
70
1
7
Order By: Relevance
“…35 mg oestradiol benzoate used in this study is based on our previous study (Alexanderson et al 2007) since this dose is known to affect insulin sensitivity and metabolism in adult female rats. There is no standardised dose or administration procedure when studying the postnatal effects of oestrogenisation, several different doses and administration regimes have been used (Arai 1964, Pinilla et al 2002, Sotomayor-Zarate et al 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 mg oestradiol benzoate used in this study is based on our previous study (Alexanderson et al 2007) since this dose is known to affect insulin sensitivity and metabolism in adult female rats. There is no standardised dose or administration procedure when studying the postnatal effects of oestrogenisation, several different doses and administration regimes have been used (Arai 1964, Pinilla et al 2002, Sotomayor-Zarate et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we showed that an early postnatal injection of oestradiol, testosterone or dihydrotestosterone causes insulin resistance in adult female rats, and that testosterone and oestradiol exposed rats also displayed increased mesenteric weight and/or adipocyte size. Oestradiol having the most pronounced effect suggests oestrogen receptors exert stronger metabolic programming effects than androgen receptors (Alexanderson et al 2007). However, the mechanisms for the effects of early exposure to sex steroids on glucose metabolism in adulthood have not been studied as yet.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Similarly, female rhesus monkeys exposed to prenatal androgen excess manifest a predominant abdominal visceral fat accumulation during adulthood, independent of obesity, reflecting a masculinized pattern of fat accumulation. 23 Importantly, NT exposure in female rats increases visceral adiposity distribution in adults 24,25 and this is true in mice, as noted above. 6 Second, in humans, females from opposite sex twin pairs exposed to prenatal testosterone from testes of a male co-twin develop masculinized eating behaviors as adults, 26 a finding we observed in our mice.…”
mentioning
confidence: 75%
“…Long-term administration of testosterone in female-to-male transsexuals induces abdominal adiposity and insulin resistance [50], and androgen excess during fetal life and infancy is associated with increased risk of developing abdominal adiposity later in life [51][52][53]. Thus, chronic androgen excess in PCOS patients could favor insulin resistance by determining a predominantly abdominal distribution of body fat (Figure 1).…”
Section: Pathophysiology Of Pcosmentioning
confidence: 99%